Retinopathy of Prematurity Scenario In A Tertiary Eye Care Hospital - Zakia Sultana; Rifat, Ahmad Masud; Ishrat Jahan; Md Zinnurain; Kousik Chowdhury; Subarna Roy; Niloy Basak (Journal of National Institute of Ophthalmology, 2025)
Purpose: To evaluate scenario of retinopathy of prematurity (ROP) in a tertiary eye care hospital. Methodology: This observational study was conducted at Department of vitreo retina in National Institute of Ophthalmology and Hospital (NIOH), Dhaka, from January 2023 to September 2023. Study population was taken among patients who had come for confirmation and treatment of ROP. The sampling method was purposive sampling. Inclusion criteria were preterm and low birth weight babies with confirmed ROP according to national guideline. Exclusion criteria was doubtful cases with peripheral avascular zone. Variables were age distribution, sex distribution, fetus count, gestational age, age during 1st examination in department of vitreo retina, birth weight, delivery place, oxygen intake, zone and stage of ROP and ROP treatment. A detailed history was taken. The clinical examination was performed and adequately recorded. A proforma was prepared to record the data on the particulars of the patients. Ethical principles were followed accordingly. Results: Maximum patients were male (62%). 25% babies were twins or triplets. Mean gestational age was 31.67 weeks. Mean birth weight was 1623 gm. Mean oxygen intake duration was 12.35 days. 81% babies had multiple complications. Maximum cases (30%) were APROP (Aggressive posterior retinopathy of prematurity ) followed by zone II stage 3 with plus disease (22%) and zone II stage 2 with plus disease (20%). Maximum patient were treated by injection Bevacizumab and ROP laser (46%) followed by ROP laser (28%) and observation (14%). Conclusion: ROP is one of the emerging causes of childhood blindness. Preterm and low birth weight babies with prolonged oxygen therapy in neonatal intensive care unit were the major cases of ROP in a tertiary eye care hospital. J.Natl.Inst.Ophthalmol. 2023; 6(2):24-31